Whiteness, Imperial Anxiety, and the "Global 1930s": The White British League Debate in Hong Kong. (April 2020) - Kong, Vivian
Abstract: What is a British colony for, and who is it for? These were the questions at the crux of a public debate in 1933 in Hong Kong sparked by a British resident claiming to have formed an organization for the "protection and advancement" of the "British white race." This article explores how anxieties about fascism, white privilege, and "others" in the empire allowed the very idea of such a political movement to be elevated to the subject of heated debate. The discussion on British unemployment, poor whites, and European "intruders" in the colony tells us less about the actual socioeconomic conditions that Hong Kong Britons faced than about their subjective experience of being "British" in an imperial context. The articulation of imperial anxiety also shows us how the fluid, ambiguous borders of whiteness and Britishness were negotiated at the intersections of nationalism, ethnicity, class, and race. Highlighting the global perspectives demonstrated in the debate and the various transnational networks across Hong Kong, this article argues that the debate was as much about global sociopolitical circumstances as about what was happening in Hong Kong. It therefore offers a timely opportunity to rethink how the local, "national, " regional, and global were interwoven in the "global 1930s, " even among the English reading public in the British colony of Hong Kong.